Data Identification of Cirebon Batik West Java Source of Strength Geographical Indication - Komarudin Kudiya; Miranda Risang Ayu (Universitas Muhammadiyah Purwokerto, 2020)
In the history of batik in Indonesia, We used to know that batik is identified with Javanese culture. In addition, the use of batik cloth is limited to the royal court with a variety of very strict rules. But in its development, batik is no longer owned by Javanese, batik has now become one of the